I survived : the Great Molasses Flood, 1919 - Tarshis, Lauren; Ball, Georgia (I survived (Graphic novel series), 2025)
When the massive metal tank filled with sticky brown molasses that rises up over her crowded North End neighborhood explodes, young Carmen must fight for her life, as a tsunami of molasses rushes through the streets.